Gesture-based Interaction Systems in Hospital Critical Environment: Challenges and Recommendations for Gesture Creation - Kimura, Karina Yukari; Moriya, Karoline Harummy Romero; Guerino, Guilherme Corredato; Teixeira, Heloise Manica Paris (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2021: Anais do XX Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2021)
Gesture interfaces contribute to touchless interaction in systems inserted in critical hospital environments such as surgery rooms and intensive care units, among other areas where infection care is essential. However, defining a vocabulary of gestures that is adequate to this environment's physical characteristics, the sensors used, and the tasks performed by users while interacting is a challenge for developers. Methodologies and guidelines proposed in the literature to the gestures definition do not consider the characteristics of the critical environment, causing natural and innovative interaction to fail by not meeting the user's need. In this sense, our paper discusses the main challenges imposed by critical environments in gesture interaction development. As a result, we propose a set of recommendations that can contribute to developers of gesture interaction systems. Moreover, our research highlights and promotes a discussion about the need to develop specific methodologies to the critical environment context that supports the definition of gesture vocabulary.